THE INFLUENCE OF PROCESSING PARAMETERS ON THE FORMATION OF SILICON DIOXIDE FROM RICE HUSK - MAZLAN, NISHA FAIRUZ (IRC, 2021)
In this project, the optimum parameters in producing high amount of silica from rice husk (RH) and the morphology of the RH was study by undergoing three different characterization process which is Thermogravimetric Analysis (TGA),